Questionnaire-Based Assessment of Wild Boar/Domestic Pig Interactions and Implications for Disease Risk Management in Corsica - Jori, Ferran; Relun, Anne; Trabucco, Bastien; Charrier, François; Maestrini, Oscar; Chavernac, David; Cornelis, Daniel; Casabianca, François; Etter, Eric Marcel Charles (Frontiers in Veterinary Science, 2017)
Wild boars and domestic pigs belong to the same species (Sus scrofa). When sympatric populations of wild boars, feral pigs and domestic pigs share the same environment, interactions between domestic and wild suids (IDWS) are suspected to facilitate the spread and maintenance of several pig pathogens which can impact on public health and pig production. However, information on the nature and factors facilitating those IDWS are rarely described in the literature. In order to understand the occurrence, nature and the factors facilitating IDWS, a total of 85 semi-structured interviews were implemented face to face among 25 strict farmers (SF), 20 strict hunters (SH) and 40 hunting farmers (HF) in the main traditional pig farming regions of Corsica, where IDWS are suspected to be common and widespread. Different forms of IDWS were described: Those linked with sexual attraction of wild boars by domestic sows (including sexual interactions and fights between wild and domestic boars) were most frequently reported (by 61% and 44% of the respondents, respectively) in the autumn months and early winter. Foraging around common food or water was equally frequent (reported by 60% of the respondents) but spread all along the year except in winter. Spatially, IDWS were more frequent in higher altitude pastures were pig herds remain unattended during summer and autumn months with limited human presence. Abandonment of carcasses and carcass offal in the forest were equally frequent and efficient form of IDWS reported by 70% of the respondents. Certain traditional practices already implemented by hunters and farmers had the potential to mitigate IDWS in the local context. This study provided quantitative evidence of the nature of different IDWS in the context of extensive commercial outdoor pig farming in Corsica and identified their spatial and temporal trends. The identification of those trends is useful to target suitable times and locations to develop further ecological investigations of IDWS at a finer scale in order to better understand diseases transmission patterns between populations and promote adapted management strategies.